1978
DOI: 10.1016/0014-4886(78)90277-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of auditory cortex unit activity during the performance of a conditioned response

Abstract: Single-unit activity in primary auditory cortex was studied in unanesthetized, paralyzed cats during the performance of a classical conditioning task. The conditioned stimulus was a 0.5-s white noise (WN) burst paired with tail shock delivered 4.5 s later. Cats habituated to WN without shock served as controls. Overlayed on these tasks was a continuous background of l/s, behaviorally irrelevant, lOO-ms duration tone bursts set to the best frequency and optimal intensity for the particular unit being studied. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
5
19
0
Order By: Relevance
“…Rather, the learning-specific change in this primary sensory neocortical region more likely reflects an enhancement in the response to the vibrissae CS input as this input gains increased behavioral significance during learning. Such an enhancement has been reported in other sensory regions after various types of learning (Disterhoft and Stuart 1976;Kitzes et al 1978;Kraus and Disterhoft 1981;Weinberger 1986, 1989;Jenkins et al 1990;Recanzone et al 1992Recanzone et al , 1993Edeline et al 1993;Gilbert, 1994, 1995;Schoups et al 2001;Ghose et al 2002;Krupa et al 2004;Rutkowski and Weinberger 2005). Since both the lesion and sham animals were able to learn delay conditioning, barrel cortical lesions did not impair the animals' ability to sense and respond to the CS.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Rather, the learning-specific change in this primary sensory neocortical region more likely reflects an enhancement in the response to the vibrissae CS input as this input gains increased behavioral significance during learning. Such an enhancement has been reported in other sensory regions after various types of learning (Disterhoft and Stuart 1976;Kitzes et al 1978;Kraus and Disterhoft 1981;Weinberger 1986, 1989;Jenkins et al 1990;Recanzone et al 1992Recanzone et al , 1993Edeline et al 1993;Gilbert, 1994, 1995;Schoups et al 2001;Ghose et al 2002;Krupa et al 2004;Rutkowski and Weinberger 2005). Since both the lesion and sham animals were able to learn delay conditioning, barrel cortical lesions did not impair the animals' ability to sense and respond to the CS.…”
Section: Discussionsupporting
confidence: 63%
“…However, hippocampal lesions made 30 d after training do not impair an animal's ability to exhibit appropriately timed CRs (Kim et al 1995;Takehara et al 2002), suggesting that long-term storage for trace associations occurs elsewhere in the brain. Various behavioral paradigms, such as frequency discrimination training (Disterhoft and Stuart 1976; Kitzes et al 1978;Weinberger 1986, 1989;Edeline et al 1993;Recanzone et al 1993;Rutkowski and Weinberger 2005) and tactile discrimination training (Jenkins et al 1990;Recanzone et al 1992;Krupa et al 2004), induce plasticity in the neocortex. These and similar studies, have led to theoretical models (Eichenbaum et al 1992;Squire et al 2004) suggesting that one of the most likely locations for long-term storage of trace associations is the neocortex.…”
mentioning
confidence: 99%
“…Slow firing changes in auditory cortex observed during the performance of other tasks Similar slow firing changes have been observed in auditory cortex with other behavioral procedures, like classical conditioning (Quirk et al, 1997;Armony et al, 1998;Kitzes et al, 1978) and instrumental conditioning in which animals were warned by an auditory stimulus and had to respond to a visual stimulus (Shinba et al, 1995) or in which animals performed an auditory working memory task (Gottlieb et al, 1989;Sakurai, 1994). Shinba et al (1995) observed slow firing increases in the auditory cortex of rats while they performed a visual detection task.…”
Section: Figsupporting
confidence: 66%
“…Conditioning-related changes in unit activity in response to auditory stimuli used as CS have been reported at many levels of the nervous system (Olds et al, 1972;Oleson et al, 1975;Disterhoft andstuart, 1976Disterhoft andstuart, , 1977Gabrielet al, 1976;Woodyet al, 1976;Kitzes et al, 1978;Ryugo and Weinberger, 1976;Weinberger, 1980Weinberger, , 1982Birt and Olds, 198 1;McCormick and Thompson, 1984;Moore, 1986, 1990;Desmond and Moore, 1986). The behavioral model of short-latency eye blink conditioning, in which relatively simple neural circuits may be involved, provides an opportunity for elucidating the primary circuitry mediating this type of conditioning.…”
Section: Neuroanatomical Representation Of Mediation Of Blink Crsmentioning
confidence: 98%